The effect of using a two-way assistive balance device on some motor abilities and improving the performance of the handstand skill in artistic gymnastics for men - muroj Muhsen; Tamadher Muhsen; Tareq Altaleb; jamal hamza (College of Physical Education and Sport Sciences, 2024)
Advanced methods in training and sports are considered one of the most important ways to succeed and reach high levels of performance in sports skills. Auxiliary devices and tools are considered training methods, as well as special exercises used with assistive devices and tools. Research objective To know the effect of using a two-way assistive balance device on some motor abilities and improving the performance of the handstand skill, But the assumption Research shows that the use of a two-way auxiliary balance device has a positive effect in improving the performance of the handstand skill in artistic gymnastics for men. Researchers experimental method (With a single group design with pre- and post-tests) to suit the nature of the problem to be solved. As for the research population, it represents (10) players affiliated with the training centers of Baghdad Governorate, Al-Karkh/Al-Rusafa for Gymnastics, and their ages range between (9 - 13) years. As for the research sample, it represented (5) players next to Al-Rusafa who train in the (Al-Amana) hall, and it was determined by (50%). The researchers used (2) players from the Al-Karkh Center for the exploratory experiment The researcher concluded The use of the two-way auxiliary balance device has clearly affected some motor abilities and improved the performance of the handstand skill in artistic gymnastics for men. The two-way balance device is of good design. Researchers recommended Conducting other studies using the device in artistic gymnastics for women and on its four devices.